Unifying the catch data of a divided island: Cyprus's marine fisheries catches, 1950-2010 - Ulman, Aylin; Cicek, Burak Ali; Salihoglu, Ilkay; Petrou, Antonis; Patsalidou, Maria; Pauly, Daniel; Zeller, Dirk (Springer, 2015)
The island of Cyprus has been divided since 1974 into the Turkish Cypriot north and the Greek Cypriot south. Here, we have reconstructed the total marine fishery removals for the island in its entirety, and then for each side. Cyprus's total marine fisheries catches were reconstructed for the 1950-2010 time period by estimating all fishery removals, including unreported commercial, subsistence and recreational catches, and major discards. These estimates were added to the 'officially reported' data, as represented by data submitted by countries to the Food and Agriculture Organization (FAO). Such data were submitted by the south, but were absent from the north for years following the 1974 partitioning of the island. The total reconstructed catch for 1950-2010 was nearly 243,000 t, which is 2.6 times the 93,200 t officially reported by FAO on behalf of Cyprus. The unreported components consisted of nearly 57,000 t of large-scale commercial landings, 43,000 t of small-scale commercial landings, 11,000 t each for recreational and subsistence landings and nearly 28,000 t of discards. Improving the accuracy of fishery statistics by accounting for all removals is fundamental for better understanding fisheries resource use thus increasing the opportunities for sustainable development through enhancing fisheries management capacity.
Keywords: Catch reconstruction; Discards; IUU; Mediterranean Sea; Unreported catches; Sustainable development